Metagenomic analysis reveals the microbiome and antibiotic resistance genes in indigenous Chinese yellow-feathered chickens - Xu, Yibin; Huang, Yulin; Guo, Lijin; Zhang, Siyu; Wu, Ruiquan; Fang, Xiang; Xu, Haiping; Nie, Qinghua (Frontiers in Microbiology, 2022)
Yellow-feathered chickens have great nutritional value and are widely and traditionally used in China, on an industrial scale as broilers. The presence of intestinal microbes has been shown to correlate with poultry performance and serves as an essential reservoir of antibiotic resistance genes (ARGs). Antibiotic resistance is a major public health concern. Here, we investigated functional characteristics of the gut microbiome of indigenous Chinese yellow-feathered chickens (the Huiyang Bearded, Xinghua, Huaixiang, Zhongshan Shanlan, Qingyuan Partridge, and Yangshan chickens) through metagenomic sequencing and reconstructed 409 draft genomes, including 60 novel species and 6 novel genera. Furthermore, we assessed the functions of the intestinal microbial communities and examined the ARGs within them. The results showed that the microbial populations of yellow-feathered broilers were primarily dominated by Bacteroidetes and Firmicutes at the phylum level and Bacteroides at the genus level. Furthermore, the Qingyuan Partridge chicken showed a significantly higher abundance of Prevotella than the other five breeds of chicken. Principal coordinates analysis indicated significant differences in the structures of microbial communities and ARGs, based on the binary Jaccard distance, among the six chicken breeds. Moreover, 989 ARGs conferring tetracycline, multidrug, and aminoglycoside resistance were identified, which represented more than 80% of the faecal resistomes; the most abundant gene in the yellow-feathered chickens was tet(Q). In addition, we found the greatest abundance of resistance genes in Xinghua chickens, indicating that Xinghua chickens are highly resistant to antibiotics. Overall, our findings revealed differences in the gut microbial community structure of indigenous Chinese yellow-feathered broiler breeds and the composition and characteristics of ARGs and antibiotic resistance that enabled us to reconstruct the yellow-feathered chicken gut microbial community genomes. The current data significantly improves our knowledge of the gut microbiome and antibiotic resistance of popular broiler breeds in China.